3D Crustal and Upper Mantle Model of East‐Central China From a Joint Inversion of Surface and Body Waves and Its Tectonic Implications. Issue 12 (21st December 2021) - Yang, Xiaozhou; Luo, Yinhe; Zhao, Kaifeng
Abstract: As the junction of two important tectonic units, North China Craton and South China Block, East‐Central China has undergone multi‐period tectonic events, including the Triassic continental collision and the Mesozoic and Cenozoic subduction of the western Pacific plate, which forms unique crustal and upper mantle structures in East‐Central China. In this study, by jointly inverting body and surface waves, we construct a high‐resolution 3D V s model of East‐Central China at the depths of 0–800 km. Our results show that along the eastern Qinling‐Dabie orogen formed by past continental collision, there are significant changes in velocity patterns in the upper mantle. From the eastern Dabie to the western Dabie, velocity features mainly vary from low velocities to high velocities, implying a westward weakening of the influence of the Paleo‐Pacific tectonic domain. The high‐velocity anomaly is partially missing beneath eastern Qinling, which may be attributed to the lower crustal and lithospheric mantle delamination. In addition, we find a significant low‐velocity anomaly in the upper mantle beneath the Lower Yangtze Craton, which may represent an upwelling of thermal fluids caused by the dehydration of stagnant slabs in the mantle transition zone. This low‐velocity anomaly extends upward into the shallow lithosphere and is consistent with the area of crustal and lithospheric thinning as well as the concentrated exposure of Cenozoic continental basalts. These connections reveal the reactivation of the lithospheric mantle by the dehydration of the stagnant slab and the asthenosphere upwelling during the Cenozoic. Plain Language Summary: East‐Central China has developed complex geological structures over a long history of tectonic evolution. Traces of past tectonic movements are preserved in the deep Earth. Imaging the present‐day subsurface structures is essential for understanding past tectonic evolution processes that occurred millions of years ago. In this study, by jointly inverting body and surface waves, we construct a high‐resolution 3D model of East‐Central China at the depths of 0–800 km. Our model shows that there is a clear change of the upper mantle structures along the eastern Qinling‐Dabie orogen, which is related to the westward subduction of Paleo‐Pacific plate. In addition, we find a low‐velocity anomaly in the upper mantle beneath the Lower Yangtze Craton. The low‐velocity anomaly may be caused by the dehydration of the stagnant Pacific slab. Altogether, our results provide new insights into the dynamic processes in East‐Central China. Key Points: A 3D velocity model of East‐Central China is obtained by a joint inversion of surface and body waves Changes in V s structure along the Qinling‐Dabie orogen suggest a westward weakening of the impact of Paleo‐Pacific plate subduction Asthenosphere upwelling induced by the dehydration of the stagnant Pacific slab during the Cenozoic reactivated the lithospheric mantle